Examining survey response styles in cross-cultural marketing research: A comparison between Mexican and South Korean respondents. (May 2018) - Beuthner, Christoph; Friedrich, Maren; Herbes, Carsten; Ramme, Iris
Modern social and marketing research relies heavily on surveys to collect data. At the same time, it is well established that survey responses are influenced by response style biases that vary across individuals, countries and cultures. Investigating such biases, we focused on Mexico and South Korea, two uprising markets mostly neglected in response style research. Data came from a survey instrument of 28 questions focusing on environmental attitudes, individual responsibilities and green packaging characteristics, administered to 500 Mexican and 525 South Korean respondents. We computed response style metrics and compared these to predictions made using scores on Hofstede and Minkov's quantitative cultural research scale. The predictions made using this scale were largely confirmed through the response style metrics. While respondents in both countries preferred answering items with "Agree" or "Strongly Agree, " respondents in Mexico were about twice as willing to "Disagree" or "Strongly Disagree" than those in South Korea. Overall, respondents in Mexico showed a bias toward extreme responses, while those in South Korea showed a response bias toward mid-point values. Our approach can be used to assist survey design and to interpret the significance of survey results. Data captured from Mexican and South Korean respondents is now available to add to the general body of knowledge on response styles.